Incidence and risk factors of retinopathy of prematurity in an Italian cohort of preterm infants - Carlo Dani; Caterina Coviello; Fiorenza Panin; Saverio Frosini; Simonetta Costa; Velia Purcaro; Domenico Lepore; Giovanni Vento (BMC, 2021)
Abstract Objective Non-negligible differences in retinopathy of prematurity (ROP) and its risk factors between different neonatal intensive care units (NICUs) are reported. Our aim was to assess the incidence and risk factors for ROP development in a large cohort of very preterm infants who were assisted in two Italian NICUs. Methods Preterm infants with gestational age between 23+ 0 and 29+ 6 weeks were stratified into subgroups of infants who developed ROP and those who did not; their clinical characteristics were compared with univariate and multivariable logistic regression analyses. Results We studied a total of 178 infants of whom 67 (38%) developed ROP (stage 1: n = 12; stage 2: n = 41; stage 3: n = 14). Regression analysis demonstrated that maternal milk (OR 0.979, 95% Cl 0.961-0.998) decreased the risk of developing ROP, while intraventricular hemorrhage (IVH) (OR 2.055, 95% Cl 1.120-3.772) increased it. Moreover, maternal milk was found to decrease (OR 0.981, 95% Cl 0.964-0.997) the risk of ROP at discharge, while RBC transfusion increased it (OR 1.522, 95% Cl 1.208-1.916). Conclusions In our cohort the occurrence of ROP was similar to that previously reported. Strategies for promoting the use of mother's own milk, preventing IVH, and standardizing the approach to RBC transfusions could contribute to decreasing the risk of ROP in very preterm infants.